Characteristics of National Standardized School Examination Test Items on Biology Subject in High School - Hidayah, Murti Ambarwati; Retnawati, Heri; Yusron, Eri (Journal of Education Research and Evaluation, 2022)
A good test instrument is required to measure students’ academic abilities. For final-year students, this ability is measured by USBN tests. This study aimed to analyses the characteristics of biology test items in the National Standardized School Examination (USBN) and analyses item tests categorized as difficult and poor. Type of study was descriptive exploratory with quantitative and qualitative approaches. Quantitative data analysis was performed using the classical test and item response theories with 1 logistic parameter model. Qualitative data analysis described why such question items are categorized as difficult and poor according to the classical test theory. The data were collected by using documentation of the answers of 193 students. The study results show that, according the classical test theory, Biology USBN item tests had the average difficulty index of 0.525 (moderate category) and the average of discrimination index obtained is equal to 0.124 (good category). Based on the item response theory, the mean difficulty index was -0.00029 (moderate category). The reliability test estimation result was 0.51, categorized as moderate. The qualitative analysis result showed that items categorized as difficult are the food web in the ecosystem, nervous system, and human excretion system.